2021
DOI: 10.3390/nano11071846
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Selective Etching and Impregnation toward Hollow Mesoporous Bioactive Glass Nanoparticles

Abstract: In this study, binary SiO2-CaO hollow mesoporous bioactive glass nanoparticles (HMBGNs) are prepared by combing selective etching and impregnation strategies. Spherical silica particles (SiO2 NPs) are used as hard cores to assemble cetyltrimethylammonium bromide (CTAB)/silica shells, which are later removed by selective etching to generate a hollow structure. After the removal of CTAB by calcination, the mesoporous shell of particles is formed. Calcium (Ca) is incorporated into the particles using impregnation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Due to the latter, it has been considered as a third generation biomaterial with immense importance in both soft and hard tissue repair and regeneration [11–13] . Hollow mesoporous bioactive glass nanoparticles have been formerly synthesized through individual or combination of templates under sol‐gel conditions [2–6,8–10] . Previous studies indicate CTAB alone [3,9,10,14] or in combination with block copolymers [5] to be effective template for generating hollow and mesoporous bioactive glass nanospheres.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the latter, it has been considered as a third generation biomaterial with immense importance in both soft and hard tissue repair and regeneration [11–13] . Hollow mesoporous bioactive glass nanoparticles have been formerly synthesized through individual or combination of templates under sol‐gel conditions [2–6,8–10] . Previous studies indicate CTAB alone [3,9,10,14] or in combination with block copolymers [5] to be effective template for generating hollow and mesoporous bioactive glass nanospheres.…”
Section: Introductionmentioning
confidence: 99%
“…Further, use of co‐templates for inducing mesoporous shell has been reported in addition to core‐forming template. In a recent study by Bocaccini et al , [8] in order to overcome the limitations of soft templates, solid silica spheres have been utilized as hard templates for synthesis of hollow mesoporous bioactive glass. The solid template provides control over size and dispersion to hollow bioactive glass nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These nanoparticles showed an absence of toxicity on MC3T3-E1 cells and lay the foundations for further applications in bone regeneration, tooth implants, and drug delivery. Mutlu et al prepared SiO 2 -CaO hollow mesoporous bioactive glass nanoparticles for bone applications using a combination of etching and impregnation strategies [ 4 ]. The authors demonstrated that differentiation of MC3T3-E1 cells occurs after incubation with these nanoparticles, showing their effectiveness in bone regeneration.…”
mentioning
confidence: 99%